A Universally Abnormality-Adaptive Logic - Batens, Diderik (Logical Investigations, 2001)
The present paper presents a logic that allows for the abnormal behaviour of any logical constant and for the ambiguous behaviour of any non-logical constant, but nevertheless offers an interpretation of the premises that is as normal as possible.
Appeared 2002